SPECIFIC CHARACTERISTICS OF THE COURSE OF MDR-TB IN ARID ZONES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Tuberculosis (TB) is one of the oldest and most dangerous infectious diseases in human history, claiming millions of lives annually. In recent decades, multidrug-resistant tuberculosis (MDR-TB) in particular has become a serious threat to global public health. MDR-TB is characterized by the resistance of mycobacteria to at least two essential first-line drugs: isoniazid and rifampicin. Treating this condition is significantly more complex, lengthy, and costly, and is associated with high rates of treatment failure and mortality
Keywords: This article provides an in-depth and expanded analysis of the existing literature on the epidemiology of MDR-TB in arid regions, its key risk factors, diagnostic challenges, treatment strategies, the impact of climate change, and regional differences. Based on real scientific sources, each significant claim in the article is supported by a citation to the relevant literature within square brackets. Global Epidemiology of MDR-TB: Current Trends